2005
DOI: 10.1002/j.2334-5837.2005.tb00770.x
|View full text |Cite
|
Sign up to set email alerts
|

10.4.2 System Integration Frameworks

Abstract: An organizations ability to effectively create, deploy and use system integration frameworks is a discriminating technical capability which will continue to grow in importance for the design, development and deployment of future engineered systems. Engineering activities utilized in large‐scale systems integration processes are strongly associated with organized problem solving and complexity reduction. This paper outlines the relationships between systems, meta‐systems, and integration frameworks as well as c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The objects that make up a system must exist before the system can be assembled. The abstraction frame concept was developed to encapsulate the flow of time in one specific context [3]. There can be multiple, concurrent abstraction frames active in any given system development.…”
Section: Abstraction Framesmentioning
confidence: 99%
“…The objects that make up a system must exist before the system can be assembled. The abstraction frame concept was developed to encapsulate the flow of time in one specific context [3]. There can be multiple, concurrent abstraction frames active in any given system development.…”
Section: Abstraction Framesmentioning
confidence: 99%
“…Context, Concept, Functions, Requirements, Architectures and Tests (CCFRAT). By emphasizing the system boundary, the CCFRAT pattern, briefly described in Figure 10, focuses on external system forces in the context portion, and focuses on the internal system forces in the concept portion (Simpson and Simpson, 2005). Context is the outward looking boundary of the system and is set by the value constraints imposed by the environment system and the production system.…”
Section: Functionsmentioning
confidence: 99%
“…Figure 12, adapted from Warfield (1990), is a notional depiction that moves from an informal type of connectivity to a formal one. Simpson and Simpson (2005) indicated that "the set of system meta-levels and meta-level transforms must be formalized in a structured fashion to support the development of a systems engineering language." Concept Map Style.…”
Section: Examples Of Se Pattern Language Relationshipsmentioning
confidence: 99%
See 2 more Smart Citations